Dziecko chłopskie w czasie profanum – konteksty edukacyjne (średniowiecze – epoka nowożytna) - Kabacińska-Łuczak, Katarzyna; Ratajczak, Krzysztof (Biuletyn Historii Wychowania, 2017)
The paper discusses the issue of functioning of the rural child during the time of the profanum, within the period from the late Middle Ages till the 19th century. The purpose of this text is to attempt to answer the questions: how did peasant children participate in the time of the profanum – understood as a time of non-celebration, and thus working time resulting from the rhythm of nature and the calendar of fieldwork, and the time of play? What did rural children learn during that time? What social and cultural skills did they acquire? The analysis of iconographic, memoir and literary sources serves the historical and pedagogical interpretation.